รูปแบบการสอนการวาดภาพลายไทย โดยใช้กิจกรรมการฝึกสมาธิด้วยหลักกายานุปัสสนา สำหรับนักเรียนชั้นมัธยมศึกษาตอนต้น TEACHING MODEL FOR THAI ORNAMENT DRAWING BY USING BODY MINDFULNESS MEDITATION PRACTICE FOR STUDENTS IN SECONDARY LEVEL - เปรมนิรันดร, อนุรุทธ; พลประเสริฐ, อภิชาติ (An Online Journal of Education, 2017)
งานวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) พัฒนารูปแบบการสอนวาดลายไทย โดยใช้กิจกรรมการฝึกสมาธิตามแนวกายานุปัสสนาเพื่อพัฒนาทักษะลายไทยของเด็กนักเรียนชั้นมัธยมศึกษาตอนต้น 2) ศึกษาผลการจัดกิจกรรมการฝึกสมาธิตามแนวกายานุปัสสนาเพื่อพัฒนาทักษะลายไทย และนําผลการจัดกิจกรรมมาพัฒนารูปแบบการสอน การวิจัยนี้ศึกษากระบวนการจัดการสอนลายไทย โดยใช้สมาธิตามหลักกายานุปัสสนาจากกลุ่มตัวอย่าง 2 กลุ่ม คือ 2.1)กลุ่มผู้เชี่ยวชาญ จํานวน 18 คน ประกอบด้วย อาจารย์มหาวิทยาลัย อาจารย์ระดับมัธยม ศิลปินด้านศิลปะไทย และพระภิกษุผู้สอนกรรมฐาน เพื่อศึกษากระบวนการจัดการสอนลายไทยโดยใช้กิจกรรมการฝึกสมาธิตามแนวกายานุปัสสนาผ่านองค์ประกอบ 5 ประการคือ จุดประสงค์การสอน, การกําหนดเนื้อหาการสอน, กิจกรรมการสอน, สื่อการสอน, การวัดประเมินผลการสอน 2.2) นักเรียนชั้นมัธยมศึกษาตอนต้น จํานวน 15 คน เพื่อศึกษา การใช้รูปแบบกิจกรรมการฝึกสมาธิตามแนวกายานุปัสสนาเพื่อพัฒนาทักษะลายไทยผ่านการทดลองสอน แล้วนํามาปรับปรุงรูปแบบการสอนให้สมบูรณ์ขึ้น จากผลการศึกษา ผู้วิจัยได้นําผลสัมภาษณ์และข้อสังเกตของผู้เชี่ยวชาญมาวิเคราะห์และนําเสนอเป็นรูปแบบการสอนวาดลายไทยที่ใช้ได้จริงตามองค์ประกอบการสอน 5 ประการดังนี้ 1) ด้านจุดประสงค์การสอน ตั้งจุดประสงค์ให้ผู้เรียนสามารถวาดลายไทยเบื้องต้นได้และเรียนรู้ประวัติศาสตร์ศิลปะไทยกับศิลปวิจารณ์ 2) ด้านการกําหนดเนื้อหาการสอน กําหนดให้ผู้เรียนเรียนรู้เนื้อหาด้านประวัติศาสตร์และทักษะปฏิบัติโดยนําสมาธิมาบูรณาการกับลายไทยด้วยการฝึกสติในการฝึกเขียนเส้น 3) ด้านกิจกรรมการสอน กําหนดให้ผู้เรียนปฏิบัติกิจกรรมการฝึกวาดลายไทยจากง่ายไปหายากอย่างเป็นขั้นตอน โดยสร้างแรงจูงใจให้ผู้เรียนด้วยสื่อที่หลากหลาย 4) ด้านสื่อการสอนวาดลายไทย เน้นให้ผู้เรียนดูสื่อภาพงานจิตรกรรมไทยและสื่อภาพเคลื่อนไหวที่หลากหลาย 5) ด้านการประเมินผลการสอน ประเมินทักษะปฏิบัติโดยดูจากผลคะแนนก่อนเรียนและหลังเรียนและประเมินจิตพิสัยโดยดูจากพฤติกรรมในชั้นเรียน หลังจากนั้นผู้วิจัยได้นํารูปแบบการสอนที่สมบูรณ์ไปทดลองสอนกับนักเรียนระดับชั้น มัธยมศึกษาปีที่ 2 โดยผลการวิจัยพบว่า 1) ผู้เรียนมีทักษะการวาดลายไทยหลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสําคัญทางสถิติที่ระดับ.05 2) ผู้เรียนโดยรวมมีความพึงพอใจในระดับมากที่สุดต่อการเรียนลายไทยจากรูปแบบการสอนวาดลายไทยตามหลักกายานุปัสสนา The purposes of this research are: 1) to develop a teaching model for Thai ornament drawing by using body mindfulness meditation practice for students in secondary level, and 2) to study the teaching result of the model developed in this research in order to improve the teaching method based on the outcome of the study. This research studied the process of teaching Thai ornament drawing by using body mindfulness meditation from 2 sample groups. The first group consisted of 18 experts in the fields of Thai arts and meditation, who were university professors, middle school teachers, Thai arts artists and monks who teach meditation. The study focuses on the process of teaching Thai ornament drawing by using body mindfulness meditation practice in 5 components: 1) Purpose of teaching, 2) contents, 3) teaching activities, 4) instructional media, and 5) teaching measurement and assessment. The second group was composed of 15 middle school students for the purpose of studying the result of the teaching model by experimenting in the class in order to improve the teaching techniques. The results of research are as follows: Analysis of the information from the interviews and observations of the sampled experts has presented the technique for Thai ornament drawing teaching. This model is practicable according to the 5 components: 1) For the purpose of teaching, the students must have preliminary skills in Thai ornament drawing and learn about the history of Thai arts and art criticism; 2) for the determination of contents the students must learn about both the history and the drawing skills, the concentration of which is integrated into Thai ornament drawing by practicing meditation while drawing; 3) for teaching activities, the students will participate in the learning activities from the easier to the more difficult ones, step by step. The learning motivation will be provided through various instructional media; 4) for the instruction media, the students will be focused at looking at various Thai ornament drawings and moving pictures; 5) for the teaching measurement and assessment, the drawing skill will be measured by the students' grades before and after the lessons and the effectiveness will be assessed by the behaviors of the students in the classroom. As a result, the researcher has applied the perfected techniques to an 8th grade classroom teaching. The research shows that.1) the students possessed higher skill of Thai ornament drawing than they did before taking classes at a significant statistical value of .05, and 2) the students, in general, were most satisfied with the teaching model for Thai ornament drawing by using body mindfulness meditation practice